Influence of Osmotic Dehydration in Processing of Tamarindus indica Jam - N. P. Minh (Journal of Global Pharma Technology, 2019)
Tamarind (Tamarindus indica L.) has long been used as a spice, food component and traditional medicine. It has high content of total phenols, proanthocyanidin and tannins Tamarindus indica has a high commercial value affordable functional foods. Howeever it has short shelf-life during post-harvest handling owing to high moisture content. It’s necessary to preserve this valuable fruit for long-term use. Objective of this research focused on the effectiveness of various processing parameters such as pretreatment with KMS solution, sugar concentration, immersion time, and agitation speed during the osmotic dehydration of Tamarindus indica into jam. Our results showed that the optimal dehydration process should be pre-treated with 0.25% KMS solution, sugar 60oBrix, immersion in 75 min, agitation 500 rpm. From this approach, the added value of Tamarindus indica fruits would be enhanced. Osmotic dehydration showed minimum heat degradation to nutritional components owing to low temperature moisture removal. It contributed some advantages such as limiting the thermal damage to the aroma, color, preventing the browning of enzymes and decreasing the energy consumption.Keywords: Tamarindus indica, Osmotic dehydration, Pretreatment, Immersion, Agitation, Sugar.